PERAN KEPALA SEKOLAH DALAM IMPLEMENTASI SUPERVISI AKADEMIK BERBASIS COACHING GUNA MENINGKATKAN KOMPETENSI PEDAGOGIK GURU SMP NEGERI 3 PEKALONGAN - Durotul Azizah; Triyono Triyono; Rika Septiyani; Soedjono Soedjono (Jurnal Manajemen Pendidikan, 2026)
Objective: This research is based on the low teaching and pedagogical abilities of teachers. This study aims to obtain an overview of the implementation of coaching-based academic supervision in improving teachers' pedagogical competence. With the background of efforts to improve teacher competence through coaching-based academic supervision. This study focuses on how to plan, implement, and obstacles in coaching-based academic supervision. The coaching-based supervision process uses the TIRTA flow. TIRTA is a coaching model which is an acronym for Objectives, Identity, Action Plan, and Responsibility. This study uses descriptive research, data is collected through coaching interviews between the principal and teachers, observations by directly observing the academic supervision process, and documentation. The researcher's findings in the field after implementing academic supervision using coaching techniques have increased the quality of learning based on qualitative findings on the quality of learning. Qualitative findings from interviews also revealed that coaching techniques in academic supervision play a role in providing convenience and helping principals and teachers develop their potential optimally.